TAHAPAN PEMBENTUKAN BRAND AWARENESS NFRT LABEL (NEFERTITI) SEBAGAI EFFORTLESS FASHION MELALUI MEDIA SOSIAL INSTAGRAM - Fidya Zahra Afifah; Yanti Setianti; Heru Ryanto Budiana (Jurnal Nomosleca, 2019)
AbstractThe vastly dynamic movement of fashion industry where many brands are converting to digital marketing, is seen as an opportunity for Indonesian local brands such as NFRT Label (Nefertiti) to build brand awareness. NFRT Label is a woman clothing line that was found in 2011. With their identity as "effortless fashion", NFRT is trying to construct's public awareness towards their brand as a clothing line with sense of effortless style through Instagram. The purpose of this research is to describe how NFRT Label builds its brand awareness as effortless fashion through Instagram. The researcher elaborates the purpose of this reserach in three aspects: how NFRT Label attracts attention on Instagram, creates consumer's comprehension and consumer's retention. This purpose is made based on Objective Awareness by Ronald.D Smith (2002). The researcher used descriptive method with qualitative data. The result of this research is elaborated based on this research's objectives. In gaining attention, NFRT creates different kinds of contents, collaborates with celebrity endorsers, holding a contest, using hashtag, creative caption-writing, et ce tera. Seeing how NFRT creates comprehension, NFRT gives basic information about their products, collection description, content consistency, creates easy-to-comprehend captions, et ce tera. To create consumer's retention, NFRT shows their signature products, does repetivite contents, manages the time and amount of postings, and use an easy-to-reccall logo. In conclusion, NFRT has done a good job in creating customer's attention through social media although NFRT hasn't given an optimal performance when creating customer's comprehension and retention.Keywords : Brand Awerness, Fashion, Social Media DOi : https://doi.org/10.26905/nomosleca.v5i1.2751